Portuguese cinema as “national cinema” - André Rui Graça (Aniki: Revista Portuguesa da Imagem em Movimento, 2016)
This essay suggest that the discussion of the issue of Portuguese cinema takes place at the most conceptual level possible, addressing its condition as national cinema and the way in which both film criticism and film studies have undertaken its analysis using this same framework. Dominant concepts and discourses will be challenged and we will assess the pragmatic importance of Portuguese cinema to audiences. In effect, more than attempting to answer the question “what is Portuguese cinema?”, this essays aims to explore what precedes the “being”, which is the reason for “existing” in the first place.